Finite element modelling of masonry cross vaults: considerations on block interlocking and interface properties - Gaetani, A. (2018)
Masonry cross vaults had been used for centuries in the roofing of European buildings, palaces and churches, representing nowadays an integral part of national cultural heritage. In this regard, a sound knowledge of the structural response of cross vaults under vertical and horizontal loads is fundamental for planning accurate and compatible conservation programs. Whereas a certain consensus on the static behavior of the cross vault under gravitational loads has been reached, still more efforts are requested for assessing its seismic capacity. In the present work, the finite element approach has been implemented with a particular attention to the block interlocking and interface elements. On the one hand, an appreciable accommodation between the real block arrangement and computational effort is shown. On the other hand, modelling the blocks with rigid-infinitely resistant elements leads the interface as the only source of physical nonlinearities. Paralleling recent works on the seismic behavior of masonry arches, the influence of the mechanical parameters of the interface elements is discussed. Comparisons between numerical and experimental results available in literature are presented in terms of ultimate strength capacity and failure mechanisms.